Design and Evaluation of Captopril-loaded Niosomes (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The goal of this study is to design a niosomal carrier system for captopril for the treatment of hypertensionthat is capable of delivering the encapsulated drug over a prolonged period of time by overcoming the limitationsof conventional dosage forms. Captopril is a water-soluble drug but has low permeability. The main objectiveis to improve bioavailability and permeability. Materials and Methods: The niosomes are prepared by thinfilm hydration method, using materials like non-ionic surfactants (Span 20, Span 40, Span 60, and Span 80) andsolvents such as chloroform and ethanol. Results and Discussion: The FTIR results revealed that there is nointeraction between captopril and excipients. All the formulations showed better encapsulation efficacy. SEManalysis revealed the size reduction of captopril-loaded niosomes. The dissolution studies showed prolonged drugrelease. Conclusion: On comprising all formulations, F3 showed sustained release of 98.44% up to 12 h. Thismay be due to the longest saturated alkyl chain and shows the highest entrapment.